UGA Read-Through Artifacts—When Popular Gene Expression Systems Need a pATCH. (May 1998) - MacBeath, Gavin; Kast, Peter
PET and similar vectors are widely used for efficient gene expression in Escherichia coli and subsequent protein purification, often by means of a C-terminal histidine (His) tag. We found that the TGA translation termination signal following the His-tag sequence in pET constructs gives rise to a significant fraction of read-through protein extended by 21 amino acids. Mass spectrometry indicated that tryptophan is inserted at the UGA (opal) stop codon in the examined non-opal suppressor strains; no evidence for translational frameshifting was detected. We have shown that the problem of obtaining heterogeneous protein preparations can easily be corrected. Plasmid pATCH1 provides a replacement sequence for the inefficient stop signal and can be used to repair both pET vectors and existing pET-based expression constructs. Our observation illustrates the largely ignored fact that a UGA codon is the worst choice for proper translation termination in efficient overexpression vectors.